TNFα G308A genotype, resilience to sleep deprivation, and the effect of caffeine on psychomotor vigilance performance in a randomized, double-blind, placebo-controlled, crossover study. (2nd October 2020) - Skeiky, Lillian; Brager, Allison J.; Satterfield, Brieann C.; Petrovick, Martha; Balkin, Thomas J.; Capaldi, Vincent F.; Ratcliffe, Ruthie H.; Van Dongen, Hans P. A; Hansen, Devon A.
ABSTRACT: The TNFα G308A gene polymorphism has been reported to influence performance impairment during total sleep deprivation (TSD). We investigated this effect in a randomized, double-blind, crossover laboratory study of repeated exposure to 48 h TSD with caffeine administration at different doses. In a retrospective analysis, we replicated the finding that the A allele of TNFα G308A, found in 4 of 12 study participants, confers resilience to performance impairment during TSD. There was no evidence of an interaction of TNFα genotype with the beneficial effect of caffeine (200 or 300 mg) on performance during TSD, suggesting distinct underlying mechanisms.